Counter Current Flow Limitation of Gas-Liquid Two-Phase Flow in Nearly Horizontal Pipe - Sigit Prayitno; R. A. Santoso; Deendarlianto; Thomas Höhne; Dirk Lucas (Science and Technology of Nuclear Installations)
Experimental work about counter current two-phase flow of air and gas in nearly horizontal pipe has been performed. The work was performed in a 1.1 m long circular transparent acrylic pipe with 50 mm inner diameter, in two inclination angle settings (20° and 10° from horizontal). The smooth liquid and air inlet was used. Porous liquid inlet and a nozzle connected with calm section were used as liquid and gas inlet. The effect of liquid properties is examined by using five different working fluids (Water, two different concentration of butanol and glycerin aqua solutions). As for results. (1) CCFL causes a drastic change in the delivered liquid to the lower plenum. (2) The effect of inclination angle is significantly observed. The flooding gas superficial velocity decreases with inclination angle. (3) The liquid viscosity affects the flooding phenomena.